Seasonal use of bridges as day-roosts by bats in the Trans-Pecos of Texas - Stevens, Richard D.; Garcia, Carlos J.; Guest, Emma E.; Hargrove, Austin; Krishnamoorthy, Macy A.; Rickert, Carl F.; Sanchez, Emma M.; Stukenholtz, Erin E.; Triplett, Colton A.; Wilson, Holly; Robertson, Stirling J. (THERYA, 2021)
Bats commonly use highway infrastructure as day- or night-roosts. Nonetheless, little is known regarding how regularly bats use these structures or whether they do so only on a seasonal basis. We surveyed 13 parallel box beam bridges along 15 km of State Highway 17 in Jeff Davis County, Texas monthly for 12 months to examine seasonality of day-roost use. Bats using bridges, ranked based on abundance, were: Tadarida brasiliensis, Myotis velifer, M. californicus/ciliolabrum, M. yumanensis, Antrozous pallidus, and M. thysanodes. Myotis velifer, M. californicus/ciliolabrum, and M. yumanensis exhibited significant differences among bridges and significant seasonality in roost use. Tadarida brasiliensis exhibited significant differences among bridges but no significant seasonality of bridge use. Seasonality of use of bridges as day-roosts likely reflects seasonal patterns of distribution of species in the Trans-Pecos. Moreover, these results suggest that surveys of bats roosting in highway infrastructure should be planned carefully and consider the seasonal nature of roost use